2018
DOI: 10.1016/j.eats.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Quadriceps Tendon Single-Bundle, Arthroscopic, Anatomic Anterior Cruciate Ligament Reconstruction With Rectangular Bone Tunnels

Abstract: Many surgeons use quadriceps tendon (QT) graft for anterior cruciate ligament (ACL) revision surgery; however, despite excellent clinical results, the QT has not achieved universal acceptance for primary ACL reconstruction. One of the reasons for this may be that the QT is technically demanding to harvest and the scar from open harvesting techniques is less cosmetically favorable than that from hamstring tendon techniques. Recent evidence has suggested that broad flat QT grafts may more closely mimic native AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Many types of grafts have been used in ACLR—autografts, allografts, and artificial ligaments—but the ideal graft, which should have structural and biomechanical similarity to the native ACL, remains debatable. Among the grafts, the most widely used are bone–patellar tendon–bone (BPTB), 7 hamstring tendon (HT), 8 and bone–quadriceps tendon, 9 as well as the recently described “half-peroneus-longus-tendon graft.” 10 There are many factors that might affect graft selection, including healing, stability, pain, and revision. Traditionally, bone-to-bone healing (BPTB graft reconstruction and bone–quadriceps tendon graft reconstruction) is considerably faster and more reliable than bone-to-tendon healing (HT graft reconstruction).…”
Section: Discussionmentioning
confidence: 99%
“…Many types of grafts have been used in ACLR—autografts, allografts, and artificial ligaments—but the ideal graft, which should have structural and biomechanical similarity to the native ACL, remains debatable. Among the grafts, the most widely used are bone–patellar tendon–bone (BPTB), 7 hamstring tendon (HT), 8 and bone–quadriceps tendon, 9 as well as the recently described “half-peroneus-longus-tendon graft.” 10 There are many factors that might affect graft selection, including healing, stability, pain, and revision. Traditionally, bone-to-bone healing (BPTB graft reconstruction and bone–quadriceps tendon graft reconstruction) is considerably faster and more reliable than bone-to-tendon healing (HT graft reconstruction).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, insertional tendinopathies such as QT and PT rupture and jumper’s knee are difficult to repair and treat. 6,17 The QT and PT, including part of the patella, are used as grafts in ACL reconstructions 4,8 and are difficult to regenerate. 5,15 Our results suggest consideration of appropriate treatment strategies based on age and the development of new treatment methods for regeneration of the tendon-bone interface and insertions.…”
Section: Discussionmentioning
confidence: 99%
“…11,32,35 While it has been suggested that a bone block is important for QT in order to increase graft stiffness, length, and anatomic fixation, 9 multiple studies have described alternative fixation techniques that maintain appropriate stiffness and anatomic fixation without any reported complications. 8,30,31,36…”
Section: Discussionmentioning
confidence: 99%